Vocational training research - Schmidt, Hermann [Mitarbeiter]; Pütz, Helmut [Mitarbeiter]; Raddatz, Rolf [Mitarbeiter] (My University, 1996)
Inhalt: SCHMIDT: Vocational training research : an instrument for innovation in the vocational training system; PÜTZ: The "inner life" of vocational training research at BIBB; RADDATZ: The involvement of the board of the Federal Institute's Research Programme. (BIBB)
Keywords: S 3.5.2.2 Bundesinstitut für Berufsbildung (BIBB); S 2.3 Berufsbildungspolitik; Bundesinstitut für Berufsbildung; Berufsbildungsforschung